2000
DOI: 10.1111/j.1348-0421.2000.tb02477.x
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiological Investigation of Feline Chlamydiosis in Cats and Humans in Japan

Abstract: The prevalence of chlamydia antibodies in Japan was investigated in 215 cat sera, consisting of 88 sera of stray cats and 127 sera of pet cats, and 2,184 human sera, taken from 2,003 general persons and 181 small animal clinic veterinarians, by microimmunofluorescence (MIF) testing with Chlamydia psittaci Fe/Pn1 of feline origin and Prk/6BC of avian origin as antigens. The prevalence rates of anti-Fe/Pnl antibodies were 45.5% in stray cats, 17.3% in pet cats, 1.7% in general persons and 8.8% in small animal cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
30
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 21 publications
1
30
0
Order By: Relevance
“…felis and both FHV-1/FCV in cats [8,18]. Our previous seroepidemiological studies indicated that feline chlamydial infection is widely spread in cats in Japan [5,15,20]. Mochizuki et al [14] reported the epidemiological status of feline URTD and Iwamoto et al [10] reported the isolation of C. felis in Japan.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…felis and both FHV-1/FCV in cats [8,18]. Our previous seroepidemiological studies indicated that feline chlamydial infection is widely spread in cats in Japan [5,15,20]. Mochizuki et al [14] reported the epidemiological status of feline URTD and Iwamoto et al [10] reported the isolation of C. felis in Japan.…”
mentioning
confidence: 99%
“…Transmission of C. felis to human was reported with conjunctivitis and serious systemic infection in an immunocompromised person [16,17]. On the basis of our previous study, feline chlamydial infection was thought to be transmitted by close contact with infected cats and possibly from infected birds [20]. Since the first isolation of FHV-1 and FCV [2,4] and the subsequent recognition of these viruses as significant causes of respiratory disease in cats [11], the relative importance ascribed to C. felis as a respiratory tract pathogen in cats has been diminished.…”
mentioning
confidence: 99%
“…The seroepidemiological surveillance of C. psittaci in cats was performed from 1980 to 1999 in Japan [3,7,13]. These reports showed the chlamydial infection in cats spread gradually and widely in Japan.…”
mentioning
confidence: 99%
“…There have been a few reports of seroepidemiological investigation of feline chlamydiosis in Japan [4,7,10,18]. Mochizuki et al reported that C. felis was found in 26.9% of diseased cats with conjunctivitis and rhinits [7].…”
mentioning
confidence: 99%
“…64(12): 1165-1168, 2002 The disease caused by Chlamydophila felis (C. felis) is clinically characterized by sneezing and coughing, accompanied by mucopurulent ocular and nasal discharges in cats [1]. Nowadays, C. felis is primarily considered an ocular pathogen with or without rhinitis in cats rather than a pulmonary pathogen [3,9,16].There have been a few reports of seroepidemiological investigation of feline chlamydiosis in Japan [4,7,10,18]. Mochizuki et al reported that C. felis was found in 26.9% of diseased cats with conjunctivitis and rhinits [7].…”
mentioning
confidence: 99%